Direct-Puncture-Guided Sharp Recanalization Technique in a Case of Long-Segment Superior Mesenteric Vein Occlusion - Mehrshad Bakhshi; Alberto Aroca; Louis-Martin Boucher (Journal of Clinical Interventional Radiology ISVIR)
We describe the case of a moderately long chronic superior mesenteric vein (SMV) occlusion following Whipple procedure. Anticoagulation therapy and traditional recanalization techniques through retrograde approach, collateral inferior mesenteric venous vasculature, and recanalization upstream of the SMV occlusion via direct transabdominal puncture failed. Sharp recanalization downstream of the occlusion via retrograde approach, using the stiff end of a glidewire sharpened with a blade, with guidance from the tip of a catheter placed upstream of the occlusion as a target was successful. Our rendezvous technique, combined with use of orthogonal views, allowed for increased precision and decreased risk of catastrophic extravasation.